Decade of the dangers of multiple magnet ingestion in children: A retrospective review. (30th December 2021) - Chang, Annette; Yeap, Evie; Lee, Eloise; Bortagaray, Juan; Giles, Edward; Pacilli, Maurizio; Nataraja, Ramesh M
Abstract : Aim: Magnet ingestion has become more frequent in children as magnetic toys and jewellery have been popularised, with the potential to cause significant morbidity. Our aim was to describe our experience at a tertiary paediatric surgical centre. Methods: Retrospective review of patients admitted with multiple magnet ingestion (January 2011‐December 2020). Division into an intervention group and conservative group. Comparisons included demographics, number of magnets and clinical outcomes. Data analysis with a Student's t ‐test and ROC Curve, P value of <0.05 was significant. Results: A total of 23 patients were identified with a total of 150 magnets ingested. The majority required an intervention for magnets retrieval (15/23, 65.2%), 11/15 (73.3%) surgical and 4/15 (26.7%) endoscopic. In the surgery group, 6/11 (54%) presented with an initial perforation and 1/11 (9.1%) an entero‐enteric fistula. One patient (9.1%) had a multi‐site anastomotic leak post‐operatively. The conservative group had a significantly lower median number of ingested magnets (2 (2–6) vs. 7 (2–40), P  = 0.03) and median length of stay (1 (1–4) vs. 7 (1–24), P =  0.03). ROC curve analysis revealed ingestion of >3 magnets had a sensitivity of 86.7% (95% CI: 62.1–97.6%) and specificity of 87.5% (95% CI: 53.0–99.4%) for requiring an intervention. Conclusion: This series highlights a significant morbidity in children with a higher incidence of intervention following ingestion of more than three magnets. There is a strong requirement for the creation and adherence to new legislature involving industry standards.